Mangrove Forest Species Composition and Density in Balok River, Pahang, Malaysia - Rozainah, M. Z.; Mohamad, M. R. (Ecoprint: An International Journal of Ecology, 2009)
Sixteen mangrove species from 10 families, including four associate species, were recorded in 4 study plots along the riverbanks of Balok river, Kuantan and Pahang. Rhizophora apiculata and Xylocarpus granatum appeared in all plots. R. apiculata shows the highest density (819 per ha) followed by R. mucronata (775 per ha). Highest species diversity was recorded in the order of plots located on downstream to the river mouth, based on the Shannon-Weiner Diversity Index. Key words: Mangrove; flora; ecology; regeneration; dominance; diversity; Pahang. doi: 10.3126/eco.v13i0.1624 Ecoprint (An International Journal of Ecology) Vol. 13, No. 1, 2006 Page: 23-28